Fish Migration, Dams, and Loss of Ecosystem Services in the Mekong Basin - Dugan, Patrick J.; Barlow, Chris; Agostinho, Angelo A.; Baran, Eric; Cada, Glenn F.; Chen, Daqing; Cowx, Ian G.; Ferguson, John W.; Jutagate, Tuantong; Mallen-Cooper, Martin; Marmulla, Gerd; Nestler, John; et al. (Springer, 2010)
The past decade has seen increased international recognition of the importance of the services provided by natural ecosystems. It is unclear however whether such international awareness will lead to improved environmental management in many regions. We explore this issue by examining the specific case of fish migration and dams on the Mekong river. We determine that dams on the Mekong mainstem and major tributaries will have a major impact on the basin's fisheries and the people who depend upon them for food and income. We find no evidence that current moves towards dam construction will stop, and consider two scenarios for the future of the fisheries and other ecosystems of the basin. We conclude that major investment is required in innovative technology to reduce the loss of ecosystem services, and alternative livelihood strategies to cope with the losses that do occur.
Keywords: Mekong; Inland fisheries; Fish migration; Dams; Ecosystem services; River development